Art, Maths, Electronics and Micros: The Late Work of Stan Ostoja-Kotkowski - Melanie Swalwell; Maria B. Garda (Switzerland, 2025)
To date, most work on computers in art has focused on the Algorists (1960s–) and on later cyber arts (1990s–). The use of microcomputers is an underexplored area, with the 1980s constituting a particular gap in the knowledge. This article considers the case of Polish-Australian artist, Stan Ostoja-Kotkowski (b. 1922, d. 1994), who after early exposure to computers at the Bell Labs (1967), returned to microcomputers late in his life. He was not a programmer yet used micros in his practice from the early 1980s, first a BBC in his BP Christmas Star commission, and later a 32-bit Archimedes. This he used from 1989 until his death to produce still images with a fractal generator and the ‘paintbox’ program, “Photodesk”. Drawing on archival research and interviews, we focus on three examples of how Ostoja deployed his micro, highlighting the convergence of art, maths, electronics, and a ‘hands-on’ tinkering ethic in his practice. We argue that when considering the history of creative microcomputing, it is imperative to go beyond the field of art itself. In this case, electronics and the hobbyist computing scenes provide crucial contexts.